Antibiotic Resistance of Human Periodontal Pathogen Parvimonas micra Over 10 Years - Thomas E. Rams; Jacqueline D. Sautter; Arie J. van Winkelhoff (MDPI AG, 2020)
Changes were evaluated over 10 years in the in vitro resistance of human periodontopathic strains of Parvimonas micra to four antibiotics. Subgingival biofilms culture positive for P. micra from 300 United States adults with severe periodontitis in 2006, and from a similar group of 300 patients in 2016, were plated onto anaerobically incubated enriched Brucella blood agar alone, or supplemented with either doxycycline (4 mg/L), clindamycin (4 mg/L), amoxicillin (8 mg/L), or metronidazole (16 mg/L). P. micra growth on antibiotic-supplemented media indicated in vitro resistance to the evaluated antibiotic concentration. P. micra resistance was significantly more frequent among patients in 2016, as compared to 2006, for doxycycline (11.3% vs. 0.3% patients; 37.7-fold increase), and clindamycin (47.3% vs. 2.0% patients; 23.7-fold increase) (both p < 0.001), whereas resistance to amoxicillin (2.3% vs. 1.0% patients) and metronidazole (0% vs. 0.3% patients) remained low and statistically unchanged between the two patient groups (p-values > 0.05). No P. micra isolates in 2006 or 2016 were jointly resistant in vitro to both amoxicillin and metronidazole. The alarming increases in subgingival P. micra resistance to doxycycline and clindamycin raise serious questions about the empiric use of these antibiotics, either locally or systemically, in the treatment of United States periodontitis patients harboring subgingival P. micra.